Difficulty in Diagnosing Secondary Peripheral Chondrosarcoma: Radiology versus Anatomical Pathology - Ruhimat, Undang; Hendarin, Arie (Journal of Medicine and Health, 2016)
Chondrosarcoma is a malignant tumor derived from bone cartilage. This tumor can be either primary or secondary. Secondary chondrosarcoma has some differences compared to the primary type i.e. the incidence is rarer, the younger age group, and many are low grade. The authors report a case of a 26-year-old man came to Hasan Sadikin Hospital with a chief complaint of a lump in the right thigh with mild pain since 5 months before consulation that is increasingly enlarging. After undergoing physical and radiological examinations, the patient was diagnosed with suspect chondrosarcoma in right thigh. Histopathologic examinations were performed 2 times, one of which used ultrasound guidance, giving a diagnosis of chondroma in right thigh. However the lesion was finally treated as chondrosarcoma. We suspected that the patient was more likely to suffer from secondary peripheral chondrosarcoma originating from malignant transformation of multiple osteochondromas. As widely known, it is almost impossible to differentiate between the low grade chondrosarcoma and chondroma with full certainty and this poses a classical problem in diagnostic medicine. Case described here was an example of the difficulty in distinguishing between these two diseases.Â Key words: secondary chondrosarcoma, peripheral chondrosarcoma, chondrosarcoma arising Â in osteochondroma